Knowledge of mother toddlers about stunting - Sri Hendrawati; Firla Husnul K.H; Witdiawati Witdiawati (Riset Informasi Kesehatan, 2020)
Background: The major issue of nutrition problem in the world is malnutrition. As many as 14% of the world's population is overweight, 13.3% of school-age children are underweight, and 35.6% are stunted. Stunting is a failure to achieve optimal growth, measured by TB/U (height by age). Mother's knowledge is an important factor in detecting stunting. Knowledge can influence the way a person understands the fulfillment of nutrition and growth in toddlers. The purpose of this study was to describe the knowledge of mothers of toddlers about stunting in children under five. Method: The study design used quantitative descriptive. The population of this study was all mothers of children under five years old in the village of Cinta Rakyat, Samarang, Garut, as many as 373 respondents, and sample was taken by proportianate purposive sampling technique to obtain 197 mothers who had toddlers. The instrument was adopted from previous reserarches by Dewi, Suhartika, and Suriani (2019). The instrument consists of 28 questions with a Guttman scale, if the correct answer is given a value of 1 and if the wrong answer is given a value of 0. The instrument validity test shows a value of 0.370-0.672 so that the instrument is declared valid, while the instrument reliability test shows a value >0.694 so that the instrument is declared reliable. Data analysis was carried out by categorizing knowledge into good, sufficient, and insufficient knowledge. Good knowledge if the answer is correct 22-28, knowledge is sufficient if the answer is correct 15-21, and poor knowledge if the answer is correct <15. Results: The results showed that the knowledge of mothers about stunting in general were 30 mothers (15.3%) had good knowledge, 59 mothers (29.9%) had sufficient knowledge, and 108 mothers (54.8%) had insufficient knowledge. Conclusion: The knowledge of mothers of toddlers about stunting in toddlers is still insufficient. Therefore, it is needed to be improved through socialization and education programs about stunting especially for mothers of toddlers that can be conducted by nurses in Community Health Center. Key words: knowledge, mother of toddlers, stunting.